Suriname : Technical Assistance Report on Government Finance Statistics Mission (December 6-17, 2021). (IMF Staff Country Reports; Country Report ;, 2022)
At the request of the Suriname authorities, a remote technical assistance (TA) mission took place during December 6-17, 2021. The mission was conducted in coordination with the IMF's Western Hemisphere Department. The main objective of the mission was to assist the Ministry of Finance and Planning (MFP) and the Central Bank of Suriname (CBS) to improve the quality of the Government Finance Statistics (GFS) in view of the IMF program. The main tasks were to (i) conduct a diagnostic assessment of the current GFS and public debt compilation process,(ii) explain and reduce statistical discrepancies, (iii) analyze data on arrears and reassess their treatment in GFS, (iv) review the integration of stocks and flows of the gross debt; and (v) update the public sector institutional table, and (vi) deliver a workshop on GFSM 2014 framework and (PSDS).